POTENSI EKSTRAK KULIT LIMAU BANJAR (Citrus reticulata) DENGAN METODE DPPH SEBAGAI ANTIOKSIDAN - Bela Ghonim Nashucha; Rakhmadhan Niah; Lutfi Anggraini; Winola Exliscia (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2019)
Free radicals are a factor that causes various degenerative diseases to occur. Degenerative diseases have become the biggest cause of death in Indonesia, such as cancer, diabetes, heart disease and premature aging. The body needs an important substance to help protect against attacks by free radicals that work by reducing the negative effects of these compounds, namely antioxidants. Natural antioxidants can be obtained through the consumption of herbal plants that contain secondary metabolites of antioxidants, such as banjar orange peel (Citrus reticulata). The aim of this study was to determine the antioxidant activity of banjar orange peel extract which was expressed by inhibitors Consentration 50 (IC50). The banjar orange peel was extracted by maceration method using aquadest solvent and antioxidant activity was tested using the DPPH (1,1-diphenyl-2-picrylhydrazly) method by UV-Vis spectrophotometry at a wavelength of 517 nm. The results showed that the banjar orange peel contained antioxidants which were 10 ppm (29,814%), 20 ppm (35,182%), 30 ppm (43,482%), 40 ppm (50,022%), 50 ppm (58,682%) with IC50 values ​​of 39,041 ppm which is included in the range of very strong antioxidant activity. The conclusion of the study is that the banjar orange peel extract has the potential to be developed as a source of natural antioxidants for humans.